Business Strategy of Limestone Project Development Case Study of CV Usaha Alam Mandiri and PT Krakatau Posco - Mulyadi, Andrew; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
This Final Project is trying to calculate the income of the project and is it feasible to be initialized or not. The calculation is begin from developing an operational process, choosing a distribution process, income statement projection, and a feasibility study of the chosen alternative.The research provides the operational process design of the project, yearly income statement projection, and developing feasibility study analysis of the project. With the right calculation, the company can generate continuous income in order to support the company growth in years to come. Â Key Words: Distribution Process, Income Statement, Feasibility StudyÂ